Hippocampal Sclerosis in Feline Epilepsy. (24th June 2014) - Wagner, Eva; Rosati, Marco; Molin, Jessica; Foitzik, Ulrike; Wahle, Andrea M.; Fischer, Andrea; Matiasek, Lara A.; Reese, Sven; Flegel, Thomas; Matiasek, Kaspar
Abstract Hippocampal sclerosis (HS) refers to loss of hippocampal neurons and astrogliosis. In temporal lobe epilepsy (TLE), HS is a key factor for pharmacoresistance, even though the mechanisms are not quite understood. While experimental TLE models are available, there is lack of models reflecting the natural HS development. Among domestic animals, cats may present with TLE‐like seizures in natural and experimental settings. With this study on the prevalence, segmental pattern and clinicopathological correlates of feline HS, we evaluated the translational value for human research. Evaluation schemes for human brains were applied to epileptic cats. The loss of neurons was morphometrically assessed and the degree of gliosis was recorded. Hippocampal changes resembling human HS were seen in about one third of epileptic cats. Most of these were associated with infiltrative diseases such as limbic encephalitis. Irrespective of the etiology and semiology of seizures, total hippocampal sclerosis was the most prevalent form seen in epileptic animals. Other HS types also occur at varying frequencies. Segmental differences to human HS can be explained by species‐specific synaptic connectivities and a different spectrum of etiologies. All these variables require consideration when translating results from feline studies regarding seizure‐associated changes of the temporal lobe and especially HS.